Gender issues in medical and public health education - Wong, Y.L. (SAGE Publications, 2000)
There is no doubt that gender bias has been inherent in medical and public health education, research, and clinical practice. This paper discusses the central question for medical and public health educators viz. whether women's health concerns and needs could be best addressed by the conventional biomedical approach to medical and public health education, research, and practice. Gender inequalities in health and gender bias in medical and public health education are revealed. It is found that in most public health and prevention issues related to women's health, the core issue is male-female power relations, and not merely the lack of public health services, medical technology, or information. There is, thus, an urgent need to gender-sensitize public health and medical education. The paper proposes a gender analysis of health to distinguish between biological causes and social explanations for the health differentials between men and women. It also assessed some of the gender approaches to public health and medical education currently adopted in the Asia-Pacific region. It poses the pressing question of how medical and public health educators integrate the gender perspective into medical and public health education. The paper exhorts all medical and public health practitioners to explore new directions and identify innovative strategies to formulate a gender-sensitive curriculum towards the best practices in medicine and public health that will meet the health needs of women and men in the 21st century.